Applied hierarchical modeling in ecology : analysis of distribution, abundance and species richness in R and BUGS.: analysis of distribution, abundance and species richness in R and BUGS. Dynamic and advanced models / Volume 2, (2018) - Kéry, Marc; Royle, J. Andrew
No abstract available